Putting the Peter Parker Principle into Practice - Maximilian Lennart Nagel; Jon Pierre (International Review of Public Policy)
Vertical coordination is a significant problem in many if not most countries. These problems are exacerbated in policy implementation related to issues that cut across jurisdictional borders. This paper compares policy implementation in the field of climate change, a quintessential example of such cross-cutting issues. In the context of CO2 emissions reduction policies, the Peter Parker principle states that vertical coordination presupposes not just central government control but also its responsibility. Our contribution to that argument is that the divorce between regulatory authority and formal jurisdiction challenges the principle. The present paper studies how these issues play out in two different types of institutional contexts; those of Germany and Sweden.